2021
DOI: 10.3390/su13105632
|View full text |Cite
|
Sign up to set email alerts
|

Do Walking-Friendly Built Environments Influence Frailty and Long-Term Care Insurance Service Needs?

Abstract: Our study examined the associations between neighborhood walkability, frailty, and the incidence of long-term care insurance (LTCI) service needs using a prospective cohort survey in a suburban town in Japan. The final sample for analyses comprised 2867 community-dwelling older adults (mean age: 73.0 years). Neighborhood walkability was measured using the Walk Score®. A total of 387 participants (13.5%) exhibited frailty. The odds of frailty, adjusted for the covariates (sex, age, educational status, marital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…Regarding the Socio-economic and Demographics topic, a variety of results were reported: there was not an association between walkability and social capital [92]; neighborhoods with high income tend to have lower walkability [93]; areas with more subsidized housing have less walkability [90]; one study notes that housing prices are positively correlated with walkability in areas with low housing prices, whereas no significant association was observed in areas with high housing prices [91], while another points to a general positive correlation between walkability and real estate prices [123]; fitness centers are less expensive and have wide opening hours in areas with higher walkability [96]; walkability has a strong positive linear effect on robbery rates and predatory violence, particularly in low-income neighborhoods [37,88,89]; walkability did not affect long-term care insurance service needs [95]; and people tend to be more extrovert in neighborhoods with higher walkability [94].…”
Section: Rq3: What Are the Main Findings From Recent Literature?mentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the Socio-economic and Demographics topic, a variety of results were reported: there was not an association between walkability and social capital [92]; neighborhoods with high income tend to have lower walkability [93]; areas with more subsidized housing have less walkability [90]; one study notes that housing prices are positively correlated with walkability in areas with low housing prices, whereas no significant association was observed in areas with high housing prices [91], while another points to a general positive correlation between walkability and real estate prices [123]; fitness centers are less expensive and have wide opening hours in areas with higher walkability [96]; walkability has a strong positive linear effect on robbery rates and predatory violence, particularly in low-income neighborhoods [37,88,89]; walkability did not affect long-term care insurance service needs [95]; and people tend to be more extrovert in neighborhoods with higher walkability [94].…”
Section: Rq3: What Are the Main Findings From Recent Literature?mentioning
confidence: 98%
“…Regarding Socio-economic and Demographics, topics of interest vary. Walkability has been associated with criminality, in the form of street crimes [37,88,89] and property incidents [40], housing availability and price [90,91], neighborhood residents' social capital [92] and economic differences [93], personality traits [94], incidence of care insurance needs [95], as well as membership costs and service availability in fitness centers [96].…”
Section: Citation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Wang et al [48] studied the relationship between walkability and the spread of COVID-19 in Massachusetts, Texas, and found that active transportation is associated with a lower infection rate during the COVID-19 pandemic. A body of literature also explored the impact of COVID-19 on walkability in urban areas and its Socioeconomic effect [49][50][51]. For example, Yuan 2022 et al [52] studied the impact of COVID-19 on walkability in Xi'an's historical area in China and found a negative impact on street vitality, which in turn caused a reduction in pedestrian flow and commercial value.…”
Section: Impact Of Covid-19 On Walkabilitymentioning
confidence: 99%
“…Such environmental strategies include improving access to healthcare and healthy food options; promoting sustainable and low-cost modes of transportation such as walking, bicycling, and public transportation; providing opportunities for physical and social activities; and improving safety of outdoor environments from crime, traffic, and injury risks. These environmental strategies are also advantageous to other health promotion strategies that tend to be individually oriented, for inducing broader population-level changes that are more likely to sustain over a long period (Andreucci et al, 2019; Mitsutake et al, 2021; Rao et al, 2007; Rebecchi et al, 2019; Renalds et al, 2010; Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%